Kebiasaan jajan berhubungan dengan status gizi siswa anak sekolah di Kabupaten Gorontalo - Nuryani, Nuryani; Rahmawati, Rahmawati (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2018)
Background : Adequate of nutrition intakes and indentification of nutrition problem in elementary school are essential for children growth and development.Objective : To analyze association between breakfast habit, dietary snacking and frequency consumption of food with nutritional status in elementary school student.Methods : Observational study with cross sectional design. The sample was collected with total sampling, included 134 student. The study was conducted in April-May 2016 which was located in Elementary School 11 Limboto, Gorontalo Regency. Antropometric measurement and nutritional status was colleted by measure of weight and height. Economic status, dietary snacking, frequency consumption of food  and breakfast habit were measured using questionare. Data analysis was used bivariate with chi square test.Results : There were 50,7% male and 49,3% female students. Around 64,9% student have accustomed breakfast, 17,9% students have frequence for eat ≥ 3 time a day and 78,4% students have accustomed snacking at the school. There was association between nutritional status with dietary snacking (p = 0,030), while dietary breakfast and frequency consumption of food with p > 0,05 that mean there was not association with nutritional status.Conclusion: dietary snacking have association with  the children nutritional status at the elementary school.